2022
DOI: 10.1186/s12890-022-02079-8
|View full text |Cite
|
Sign up to set email alerts
|

The performance of detecting Mycobacterium tuberculosis complex in lung biopsy tissue by metagenomic next-generation sequencing

Abstract: Background Tuberculosis (TB) is a chronic infectious disease caused by the Mycobacterium tuberculosis complex (MTBC), which is the leading cause of death from infectious diseases. The rapid and accurate microbiological detection of the MTBC is crucial for the diagnosis and treatment of TB. Metagenomic next-generation sequencing (mNGS) has been shown to be a promising and satisfying application of detection in infectious diseases. However, relevant research about the difference in MTBC detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…19 Notably, the accuracy of mNGS for PTB diagnosis was high. 28 Similar to PTB, previous studies had suggested that mNGS had good diagnostic performance in spinal TB. 19 These results were comparable to the findings of this study.…”
Section: Discussionmentioning
confidence: 88%
“…19 Notably, the accuracy of mNGS for PTB diagnosis was high. 28 Similar to PTB, previous studies had suggested that mNGS had good diagnostic performance in spinal TB. 19 These results were comparable to the findings of this study.…”
Section: Discussionmentioning
confidence: 88%
“…The combined sensitivity and specificity of the summarized primary results were 0.69 [0.58-0.79] and specificity 1.00 [0.99-1.00] respectively (Figure 3). Because there were 5 studies with a high risk of bias in the patient domain, 3 studies with a high risk of bias in the test domain, 3 studies with an unknown risk of bias in the reference domain, and 7 studies with unclear case flow and timing domains or High risk and large bias, moderately conclusive evidence downgraded (12,13,15,19,(22)(23)(24)(25)(26). Supplementary Table S2 shows the subgroup analysis of potential sources for evaluating sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In China, approximately 60% of pulmonary TB cases were bacteriologically negative in 2018 9 , indicating that many patients with TB negative should be misdiagnosed and delayed treatment. With the advantages of hypothesis-free, culture-independent, and unbiased pathogen detection directly from clinical specimens, clinical metagenomics next-generation sequencing (mNGS) has been applied to diagnose tuberculosis [10][11][12][13][14] . Some studies showed that the sensitivity and speci city of mNGS were comparable to that of the Xpert MTB/RIF assay (Cepheid, Sunnyvale, CA.…”
Section: Introductionmentioning
confidence: 99%